PENGARUH EMOTIONAL EXHAUSTION DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Christianto, Gunawan; Putra, Made Surya (E-Jurnal Manajemen; Vol 5 No 5 (2016), 2016)
Job satisfaction is one indicator of the success of the company's operations in an effort to achieve its objectives. To realize that employee job satisfaction can be achieved, then the company must consider the factors that can influence job satisfaction. The purpose of this study was to determine the influence of emotional exhaustion and work motivation on employee job satisfaction. The study was conducted at CV. Mahesa Company Group Denpasar. The number of samples taken as many as 35 employees. Mechanical sampling using saturated sample. Data collected through interviews and field surveys. Data were analyzed using multiple linear regression. The results showed the variables emotional exhaustion negatively affect employee job satisfaction, work motivation while a positive effect on employee job satisfaction. Based on the research results, the suggestions to be considered by the company is the imposition of work must be in accordance with the expertise and field employees, providing specific training to employees and salaries should be adjusted to the workload of employees.
Keywords: Emotional Exhaustion, Work Motivation, Job Satisfaction